Protective effects of 18β-glycyrrhetinic acid on pulmonary arterial hypertension via regulation of Rho A/Rho kinsase pathway. (25th September 2019) - Zhang, Min; Chang, Zhi; Zhang, Peng; Jing, Zhicheng; Yan, Lin; Feng, Jun; Hu, Zhiqiang; Xu, Qingbin; Zhou, Wei; Ma, Ping; Hao, Yinju; Zhou, Ru
Abstract: Purpose: Excessive proliferation, migration and anti-apoptosis of pulmonary artery smooth muscle cells (PASMCs) are the basis for the development of pulmonary vascular remodeling, and it is the driving force for pulmonary arterial hypertension (PAH). 18β-glycyrrhetinic acid (18β-GA) is the main active substance extracted from Chinese herbal medicine licorice, with outstanding anti-inflammatory, anti-oxidation and anti-proliferative effects. Our team found in previous studies that 18β-GA has protective effects on monocrotaline-induced PAH in rats. However, the anti-angiogenic effect of 18β-GA on PAH remains unclear. Therefore, in order to further investigate whether the beneficial effects of 18β-GA on PAH are related to its antiproliferative effect, we conducted experiments in vivo and in vitro. Methods and results: In vivo, 18β-GA relieved mean pulmonary arterial pressure, right ventricular systolic pressure, and right ventricular hypertrophy index, improving pulmonary remodeling. In vitro, 18β-GA significantly inhibited PDGF-BB-induced proliferation and DNA synthesis of HPASMCs, blocking the progression of G0/G1 to S phase of the cell cycle. Furthermore, after treatment with 18β-GA, the expression of Rho A, ROCK1, ROCK2 was decreased and ROCK activity was inhibited in HPASMC. In addition, 18β-GA also attenuated PDGF-induced changes in p27 kip1, Bax and Bcl-2. Conclusions: In summary, these results indicate that 18β-GA regulates the activity of RhoA-ROCK signaling pathway, inhibits the proliferation of HPASMCs, and has potential value in the treatment of PAH. Graphical abstract: Image 1 Highlights: 18β-GA inhibits the proliferation of PDGF-BB induced HPASMCs. 18β-GA reversed the pathological changes in pulmonary vascular remodeling. 18β-GA inhibited the activation of RhoA/ROCK signaling pathway.